ANALISIS HUBUNGAN ASPEK PERILAKU PETANI HORTIKULTURA DENGAN KEBERHASILAN POLA KEMITRAAN DI ASOSIASI ASPAKUSA MAKMUR KABUPATEN BOYOLALI - Vrisqa Ridha Ramadhanty (SUNGKAI, 2020)
This research aims to (1) analyze the level of knowledge, attitudes, skills of horticultural farmers with the Aspakusa Makmur Association (2) analyze the success of the partnership pattern of horticultural farmers with the Aspakusa Makmur Association (3) analyzing the relationship of behavior of partner farmers with the success of partnership patterns in the Aspakusa Makmur Association The study was conducted in March-April 2019 at the Association of Aspakusa Makmur in Boyolali District. The method used in the research is survey. Data collection through interviews using a questionnaire. Sampling is done using the Complete Enumeration method by taking all members of the population as the study sample. All members of the Aspakusa Makmur Association farmer group numbered 35 respondents. Data were analyzed descriptively and quantitatively. The results showed that the level of knowledge of farmers in the Aspakusa Makmur Association was high, the level of attitudes of farmers in the Aspakusa Makmur Association was also high and the skill level of farmers in the Aspakusa Makmur Association was high, while farmers 'behavior had a positive relationship with farmers' knowledge and skills with success patterns unidirectional partnership.